"We are not privileged enough to have that foundation of language": Pasifika young adults share their deep concerns about the decline of their ancestral/heritage languages in Aotearoa New Zealand. (June 2019) - Samu, Lina-Jodi Vaine; Moewaka Barnes, Helen; Asiasiga, Lanuola; McCreanor, Tim
Focus group interviews conducted with Aotearoa New Zealand–born Pasifika young adults aged 18–25 years highlighted their intense apprehension about the diminishing abilities of New Zealand–born Pasifika people to speak their ancestral/heritage Pasifika languages in Aotearoa. Some Pasifika languages are also declining at their homeland wellsprings. There has been no comprehensive strategic national language policy developed in New Zealand where Pasifika heritage and other community languages can flourish. New Zealand appears to default to a monocultural given where English prevails without critique. Minority languages are battling it out with each other for legitimacy of existence. Resulting from New Zealand's failure to create a comprehensive languages strategy for all, younger generations of Pasifika neither have fluency in their ancestral languages which impact negatively on their identity security and their ability to attain critical fluency in English to thrive as their migrant parents and grandparents envisioned they would in Aotearoa New Zealand.